Reputation, Debt, and Policy Conditionality - Ramcharan, Rodney (IMF Working Papers; Working Paper ;, 2003)
In principle, international financial institutions (IFIs) can use their leverage as creditors to prompt governments to undertake policy reform. Yet such lending has been frequently linked to unsustainable debt levels and little reform. This paper illustrates how the dual roles of IFIs as purveyors of credit and monitors of reform may help explain these negative outcomes. When debt levels rise, the IFIs reforms goals may become subordinated to its creditor's interest, compromising the enforcement of conditionality. Attracted by this prospect, malevolent governments strategically reform, enhancing their reputation in order to maintain lending and build their debt stock. Once debt levels are sufficiently large, such governments can stop policy reforms, assured that lending will continue.